Redefining Consumer Utility in the Perspective of Islamic Economics Framework - Muttaqin, Zein; Pusparini, Martini Dwi (Universitas Ahmad Dahlan, 2019)
An interest of individual preferences which can be represented in numerical ways known as the utility. While others stated it as a matter of subjective feeling that being felt in order to pursue and to maximize the certain level of satisfaction and personal well-being. According to neoclassical theory, this happened due to the contraction consumer preferences between things/products/services that available in the market. Furthermore, the ultimate ends that have been proposed are that the industry/market is spiritually neutral. On the other hand, some of Muslim scholars argue that spiritual or religious values are what defines an individual as a human, while all conducted of consumption is abide by ethics and religious values, which will not forsake others for personal gains. The integration of religious aspect in pursuing of maximization of utility is known as maslahah (i.e. well-being). A further discussion that arises is in Islamic economics framework, does individual orients solely to maximize their utility, even in the sense of maslahah is considered. Neoclassical claims that to interpret the utility, there are two headings is considered, they are prediction approach and prescription approach. The debate on neoclassical and Islamic economics perspectives might contradict one to another, but none of it is at absolute truth, the theory itself is still developing due to different assumptions and circumstances that present at that time. Furthermore, the revisiting theory of maqasidh al-sharia (i.e. the objective of Islamic Laws) also provides a different point of view regarding the debatable utility between neoclassical and Islamic economics. In pursuance of better understanding of utility, this article aims to redefine the consumer utility in Islamic economics framework. It can be concluded that the definition of utility under Islamic perspective as the act to seek self-actualization of benefit which collide to the benefit of others in pursuing of enhancement of dual dimensions objectives of present and hereafter. A strong point that being found that in order to maximize the utility/maslahah must consider the possibility of misleading the genuine motive of utility, which is not adjusting it under social pressures. The misleading act of such is categorized as the act of falsification of preferences.